Integrative Genomics: In Silico Coupling of Rat Physiology and Complex Traits With Mouse and Human Data - Twigger, Simon N.; Nie, Jeff; Ruotti, Victor; Yu, Jiaming; Chen, Dan; Li, Dawei; Mathis, Jed; Narayanasamy, Vijay; Gopinath, Gopal R.; Pasko, Dean; Shimoyama, Mary; de la Cruz, Norberto; et al. (Genome Research, 2004)
Integration of the large variety of genome maps from several organisms provides the mechanism by which physiological knowledge obtained in model systems such as the rat can be projected onto the human genome to further the research on human disease. The release of the rat genome sequence provides new information for studies using the rat model and is a key reference against which existing and new rat physiological results can be aligned. Previously, we described comparative maps of the rat, mouse, and human based on EST sequence comparisons combined with radiation hybrid maps. Here, we use new data and introduce the Integrated Genomics Environment, an extensive database of curated and integrated maps, markers, and physiological results. These results are integrated by using VCMapview, a java-based map integration and visualization tool. This unique environment allows researchers to relate results from cytogenetic, genetic, and radiation hybrid studies to the genome sequence and compare regions of interest between human, mouse, and rat. Integrating rat physiology with mouse genetics and clinical results from human by using the respective genomes provides a novel route to capitalize on comparative genomics and the strengths of model organism biology.